The Good, the Bad, and the Ugly of Urbanization: Response of a Bird Community in the Neotropical Andes - Ordóñez-Delgado, Leonardo; Iñiguez-Armijos, Carlos; Díaz, Mario; Escudero, Adrián; Gosselin, Elyce; Waits, Lisette P.; Espinosa, Carlos Iván (Frontiers in Ecology and Evolution, 2022)
Urbanization constitutes one of the most aggressive drivers of habitat and biodiversity loss worldwide. However, studies focused on determining the response of local biodiversity to urbanization are still scarce, especially in tropical ecosystems. Urban ecosystems are characterized by low biological productivity which in turn leads to a reduction in diversity. However, the responses to urbanization should be species dependent. For instance, changes in the availability of resources can favor certain species with specific characteristics. We assessed the effects of the urbanization process on a bird community in a city located in the Tropical Andes of southern Ecuador, a region widely recognized for its diversity and endemism of birds. We selected three independent localities in each of the four levels of the urbanization gradient in the study area (forest, forest-pasture, pasture, and urban). In each locality, we sampled the bird community by visual and auditory surveys along 1 km transects between 2016-2017. We recorded a total of 1,257 individuals belonging to 74 bird species. We evaluated if the responses of richness and abundance of birds are dependent on trophic guild and foraging strata. We found a significant decrease in bird species richness and abundance from forest to urban sites. However, the response of birds was dependent on the trophic guild and forging strata. Granivorous showed a positive effect associated with the urbanization gradient while insectivorous showed a negative effect. Insectivorous were more abundant in forest sites and decreased in abundance across the urbanization gradient. We found that the proportion of birds using different foraging strata drastically changed along urban gradient. Forest sites exhibited a bird community using a variety of habitats, but the bird community became simpler towards the most urbanized sites. Our findings showed different effects of urbanization on bird communities. The ugly: urbanization leads to a dramatic reduction in the diversity of birds, which is consistent in cities with different characteristics and ecological contexts. On the other hand, the responses of bird guilds to urbanization are species dependent. Some guilds are positively impacted by urbanization and show increases in species richness and abundance while other guilds are negatively impacted.